Ijtihad Bayani Sebagai Metode Penemuan Hukum Islam - Zulfahmi Bustami; andrizal, andrizal; Mawardi, Mawardi M Saleh (Jurnal Hukum Respublica, 2023)
The discovery of Islamic law is also known as the Al-Bayan law discovery method which includes efforts to understand the sources of legal guidance or tasyri', namely the Qur'an and As-Sunnah. These two main sources are references in establishing law. As the main source in legal development, it must be well understood, so that legal issues can be solved appropriately. So the purpose of this article is to discuss ijtihad bayani as a method of discovering Islamic law. This type of research is library research. The method used in this article is descriptive qualitative. The results of this study state that bayani reasoning in Islamic law is to explain the meanings contained in the texts of the Koran and hadiths as one of the objectives of transmitting shari'a to mankind. The form of bayani reasoning in Islamic law is a basic competency that must be possessed by mujtahids in carrying out ijtihad in all conditions and times.